Description of Sinometrius donggongensis sp. n. (Coleoptera, Carabidae, Paussinae) from the Donggong Mountains, East China - Song, Xiao-Bin; Peng, Zhong (Zootaxa, 2021)
Wrase and Schmidt (2006) established the genus Sinometrius Wrase & Schmidt, 2006 to include the new species S. turnai Wrase & Schmidt, 2006 from Hubei province, central China. They placed the new genus in the Paussine tribe Metriini, and compared it to the Nearctic genus Metrius Eschscholtz, 1829. Deuve (2020) described a second species S. jaroslavi Deuve, 2020 from Chongqing province.